El impacto de la acción de repetición en la Fiscalía General de la Nación durante el periodo 2015 a 2016 (2017)
The present work seeks to analyze the demands that are being received against the nation and validate the processes that are carried out to try to recover the large sums of money that the State has paid for convictions. proffered against him, particularly in the Defense, Justice and Security Sector and more exactly within one of the entities that dishonorably is one of the entities that receives the most sanctions against him. Huge amounts of money year after year must be canceled due to penalties due to the unlawful damages caused to people either with intent or serious guilt for the actions or omissions of their agents. It is for this reason that this work will be analyzed in 2015 and 2016, within the Office of the Attorney General of the Nation and the impact that the action of repetition has had on this entity in order to recover the large amounts of money that for said lawsuits must be canceled, their action plans and the commitments that this entity has acquired to try to reduce the number of lawsuits against them.